Earlier Initiation of Postoperative Physical Therapy Decreases Opioid Use after Total Knee Arthroplasty - Frenkel Rutenberg, Tal; Izchak, Haim; Rosenthal, Yoav; Barak, Uri; Shemesh, Shai; Heller, Snir (The Journal of Knee Surgery, 2020)
For patients with advanced osteoarthritis of the knee, total knee arthroplasty (TKA) has been shown to provide significant pain relief and improved function with consistent, reproducible results. Post-operative physical therapy (PT) plays an important role is restoring muscle strength and range of motion (ROM). Yet, the impact of earlier physical therapy initiation after TKA has not been well defined. We assessed 205 patients that underwent primary TKA including 136 patients who started PT on the first post-operative day (POD1) and a second group that started PT 3 days after surgery (POD3), or later. Length of hospital stay (LOS), opioid use during hospital stay, complications, re-admissions, knee ROM and the need for subsequent hospitalized rehabilitation were recorded. LOS was not significantly shorter in the early PT group, compared with the delayed PT group (6.4 ± 2.2 days vs. 6.8 ± 2 days, respectively, P = .217). Patients in the delayed PT group consumed more opioids during their inpatient stay compared with the early PT group on both POD 3 (89% vs 82%, p = 0.013) and POD 4 (81% vs 66%, p = 0.005). There was no significant difference in the incidence of Immediate post-operative complications or final knee ROM between the two groups. While early postoperative PT did not impact hospital LOS or final knee ROM, it was associated with an earlier reduction in postoperative opioid consumption after primary TKA.
Keywords: total knee arthroplasty; postoperative physical therapy; pain; opioids; length of stay